Susceptibility of community associated methicillin resistant Staphylococcus aureus isolated from faeces to antiseptics - Ezekiel Olugbenga Akinkunmi; Adebayo Lamikanra (Journal of Infection in Developing Countries)
Introduction: The study aimed to investigate the resistance of methicillin resistant Staphylococcus aureus (MRSA), an indicator used in hospitals but isolated from faecal samples of children in the community, to commonly used antibiotics and antiseptic agents.